Livelihoods, vulnerability and adaptation to climate change in the Morogoro region, Tanzania - Jouni Paavola (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
This paper examines livelihood responses to climate variability and other stressors in the Morogoro region in south-eastern Tanzania, with an aim to understand the implications of these responses to adapting to changing climate in the region in the future. The paper indicates how farmers have responded to draughts by expanding cultivations, reducing fallows, switching crops and engaging in wage employment or in charcoal, timber and brick production. Farmers also frequently migrate on temporary basis to locations which have favourable farming conditions or better access to markets. More permanent migration to towns and cities has also increased. Farming practices and heavy reliance on forest resources have resulted in soil erosion and deforestation which have reduced water retention, increased flooding after rains and reduced water flow between the rains. These environmental changes complicate living with increased climate variability in the future because reduced natural resource base may not be able to provide the same safety net functions as it currently provides during periods of stress. This would be particularly problematic for those who live in more remote rural villages and who suffer from limited access to markets, public services and utilities. Efforts to reduce vulnerability to increased climate variability in the region would need to safeguard the natural resource base, promote market access and augment human capital. Natural resource base demands attention because its safety net functions are important to large proportions of rural and urban population and because the loss of ecosystem services would increase the exposure of large downstream populations to floods and scarcity of water. The promotion of market participation can provide incentives to diversification and intensification and help reduce dependence on risky agricultural production. Finally, diversification of livelihoods is constrained by deficiencies in physical health, skills and knowledge. Therefore, public spending and programs related to health, education and wellbeing can facilitate diversification in the future.
Keywords: 330; Adaptation to climate change; livelihoods; social justice; Tanzania; vulnerability